Training of Teachers and Teaching Career in Chile: Training Programs in Regions (Revista LIDER, 2018)
The article that follows is part of a qualitative research on initial teacher training in Chile; a vision of the process taking into account the problems at the time of implementation from various policies, ranging from the international to the regional scale are shown. We then focus on the current situation in the region of Los Lagos, in the supply of teaching careers and we close this article with alternatives for the provision of teacher training.